2020
DOI: 10.1371/journal.pone.0228758
|View full text |Cite
|
Sign up to set email alerts
|

Can intestinal absorption of dietary protein be improved through early exposure to plant-based diet?

Abstract: Nutritional Programming (NP) has been studied as a means of mitigating the negative effects of dietary plant protein (PP), but the optimal timing and mechanism behind NP are still unknown. The objectives of this study were: 1) To determine whether zebrafish (Danio rerio) can be programmed to soybean meal (SBM) through early feeding and broodstock exposure to improve SBM utilization; 2) To determine if NP in zebrafish affects expression of genes associated with intestinal nutrient uptake; 3) To determine if ear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Kwasek et al 7 later followed that notion in zebrafish and investigated the effect of NP on the expression of appetite-stimulating hormones and found that during the PP challenge period, an upregulation and/or downregulation was observed for ghrelin, cholecystokinin, and neuropeptide Y in the intestine and/or brain. Moreover, both Kwasek et al 7 and Molinari et al 8 reported improved morphological adaptation of the intestine in zebrafish reflected by higher villus length to width ratio in programmed versus nonprogrammed groups possibly allowing for more efficient dietary SBM breakdown and nutrient absorption. Furthermore, Molinari et al 8 found that the expression of Pept1, an intestinal peptide transporter used as an indicator of nutritional status in fish, 38,39 at 60 dph was higher in zebrafish that were previously exposed to dietary SBM during their juvenile stage (13-23 dph).…”
Section: Nutritional Programming On Zebrafish 133mentioning
confidence: 99%
See 4 more Smart Citations
“…Kwasek et al 7 later followed that notion in zebrafish and investigated the effect of NP on the expression of appetite-stimulating hormones and found that during the PP challenge period, an upregulation and/or downregulation was observed for ghrelin, cholecystokinin, and neuropeptide Y in the intestine and/or brain. Moreover, both Kwasek et al 7 and Molinari et al 8 reported improved morphological adaptation of the intestine in zebrafish reflected by higher villus length to width ratio in programmed versus nonprogrammed groups possibly allowing for more efficient dietary SBM breakdown and nutrient absorption. Furthermore, Molinari et al 8 found that the expression of Pept1, an intestinal peptide transporter used as an indicator of nutritional status in fish, 38,39 at 60 dph was higher in zebrafish that were previously exposed to dietary SBM during their juvenile stage (13-23 dph).…”
Section: Nutritional Programming On Zebrafish 133mentioning
confidence: 99%
“…Moreover, both Kwasek et al 7 and Molinari et al 8 reported improved morphological adaptation of the intestine in zebrafish reflected by higher villus length to width ratio in programmed versus nonprogrammed groups possibly allowing for more efficient dietary SBM breakdown and nutrient absorption. Furthermore, Molinari et al 8 found that the expression of Pept1, an intestinal peptide transporter used as an indicator of nutritional status in fish, 38,39 at 60 dph was higher in zebrafish that were previously exposed to dietary SBM during their juvenile stage (13-23 dph). The limited studies available therefore suggest that the mechanism behind NP might be associated with endocrine and morphological adaptation of the digestive system that leads to enhanced digestion and absorption capacity ultimately reflected by improved growth performance.…”
Section: Nutritional Programming On Zebrafish 133mentioning
confidence: 99%
See 3 more Smart Citations